PHILOSOPHICAL REFLECTIONS ON JOURNALISTIC COMPETENCE IN RIAU'S MEDIA LANDSCAPE - Eka Putra (LLDIKTI Wilayah X, 2023)
The competence of journalists is very important to ensure that the information that is presented to the public is accurate, balanced and of a high quality. Journalistic competence includes aspects of awareness, knowledge and skills that underpin accurate, objective and responsible reporting. In the context of the research in Riau Province, it was found that although it is recognised that journalistic competence plays a crucial role in ensuring accurate, balanced and quality information to the public, there is a gap in understanding among journalists in the region. In particular, this research highlights that journalists in Riau Province still face obstacles in fully understanding aspects of journalistic literacy. Data analysis using the qualitative method of in-depth interviews with the help of Nvivo 12 software shows that there is room for improvement in understanding the awareness, knowledge and skills that underlie accurate, objective and responsible reporting. Importantly, the need for a broader approach to all journalists is highlighted, suggesting that the solution to this gap is not only individual but also systemic. There is a need to develop strategies and programmes that involve the entire journalistic community in Riau Province so that the understanding of journalistic competence can be improved together. In addition, the application of competency scores also did not yield sufficient results, indicating the need for further evaluation of the journalist performance evaluation method. Therefore, this article is a call for a deeper change in approach to improve the understanding and application of journalistic competence in Riau Province. Through this contribution, it is hoped that research can provide a solid foundation for concrete steps to increase press professionalism in Riau Province, in line with the provisions of Press Law No. 40 of 1999.